1984
DOI: 10.1111/j.1476-5381.1984.tb16496.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of vasoconstriction by frusemide in the rat

Abstract: 1 Mesenteric blood flow was measured in anaesthetized rats with a non-cannulating electromagnetic flow probe around the superior mesenteric artery. Reductions in blood flow were produced by intravenous bolus injections of angiotensin II (1 -300ng) and noradrenaline (3 -300ng)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

1987
1987
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 19 publications
2
12
0
Order By: Relevance
“…In addition to venodilation, several investigators have reported increases in blood pressure and vascular resistance (34, 52) after loop diuretic treatment. The reduction in contractility of isolated Nkcc1 Ϫ/Ϫ portal veins is consistent with the hypothesis that the increased venous compliance in response to loop diuretics is due to inhibition of NKCC1 in the vasculature; however, the results of several studies (5,16,23) suggest that these effects might also be due to the release of vasoactive compounds from the kidney. If the kidney is involved, then inhibition of NKCC1, which is expressed in the extraglomerular mesangium and the glomerular afferent arteriole (25), could contribute to this effect.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…In addition to venodilation, several investigators have reported increases in blood pressure and vascular resistance (34, 52) after loop diuretic treatment. The reduction in contractility of isolated Nkcc1 Ϫ/Ϫ portal veins is consistent with the hypothesis that the increased venous compliance in response to loop diuretics is due to inhibition of NKCC1 in the vasculature; however, the results of several studies (5,16,23) suggest that these effects might also be due to the release of vasoactive compounds from the kidney. If the kidney is involved, then inhibition of NKCC1, which is expressed in the extraglomerular mesangium and the glomerular afferent arteriole (25), could contribute to this effect.…”
Section: Discussionsupporting
confidence: 64%
“…Additional studies will be needed to determine the extent of the deficit in vascular contractility, the ionic basis for this defect, and whether it is the major mechanism of the observed hypotension. Given the expression of NKCC1 in renin-secreting cells of the glomerular afferent arteriole, it seems possible that alterations in the secretion of vasoactive compounds from the kidney might, as suggested by others (5,16,23), account for some of observed vascular effects of loop diuretics in vivo. The reduction in excitatory amino acid release observed in Nkcc1 Ϫ/Ϫ astrocytes (49) suggests that neuronal mechanisms could also be involved.…”
Section: Discussionmentioning
confidence: 99%
“…However, as pointed out earlier, several authors recently have not been able to detect any change using GC-MS techniques. Furthermore, although indomethacin pretreatment can prevent the vasoconstrictor-inhibitory effect of frusemide (Gerkens & Smith 1984;Armsworth et al 1986) recently we have shown, using the ex vivo blood perfused tail artery, that indomethacin administration, after the effect of frusemide is established, does not reverse this effect, despite evidence of complete cyclo-oxygenase blockade (Gerkens et al 1986). The evidence therefore indicates, first, that prostaglandins may be involved in the release ofa renal hormone but that the antivasoconstrictor effect of frusemide on peripheral arteries is not mediated by prostaglandins and, second, that the vascular effect of the unidentified hormone depends on an intact endothelium.…”
Section: Nor Normentioning
confidence: 96%
“…Our understanding of the mechanisms responsible for the venodilation and regional arteriolar vasoconstriction observed in response to acute furosemide administration is still incomplete. However, the venodilatory response is dependent on intact kidneys since the response is abolished in anephric patients (Johnston et al 1983) and by nephrectomy in dogs and rats (Bourland et al 1977;Bayne & Williamson 1979;Gerkens & Smith 1984;Armsworth et al 1986;Gerkens et al 1987), but not by uretheral ligation in dogs (Bourland et al 1977;Bayne & Williamson 1979). Furthermore, the arteriolar vasoconstriction after acute furosemide administration is absent in anephric patients (Johnston et al 1983) and it is inhibited by nephrectomy in dogs (Ludens et al 1970).…”
Section: Effects Of Furosemide On Systemic and Renal Hemodynamicsmentioning
confidence: 99%
“…Gerkens and colleagues have demonstrated that furose-9 mide inhibits vasoconstrictor responses to sympathetic stimulation in the in situ blood perfused mesenteric artery and that this response in blocked by bilateral nephrectomy, chemical renal medullectomy with bromethylamine, and by indomethacin (Gerkens & Smith 1984;Armsworth et al 1986;Gerkens et al 1987). To examine the role of the endothelium for furosemide-induced vasodilation, the same investigators performed an experiment using periarterial electrical stimulation of the sympathetic nerves of a tail artery which was cross-perfused ex vivo with blood from an anesthetized donor rat.…”
Section: Effects Of Furosemide On Systemic and Renal Hemodynamicsmentioning
confidence: 99%